Hereditary neuropathies caused by mutations in the gene encoding peripheral myelin protein 22 - Bjelica, Bogdan; Rakočević-Stojanović, Vidosava (Medicinski podmladak, 2024)
Mutations in the gene encoding peripheral myelin protein 22 (PMP22) can manifest as Charcot-Marie-Tooth neuropathy (CMT) 1A (CMT1A), in case of duplication, or hereditary neuropathy with liability to pressure palsies (HNPP), in case of deletion. In rare cases, point mutations in the PMP22 gene can occur, which can cause CMT1E and Déjerine-Sottas syndrome (DSS). CMT1A and HNPP represent the most common inherited neuropathies. The age of onset of CMT1A is manly in the first two decades, and the clinical features typically include atrophy and weakness of distal muscles with or without loss of sensation, foot deformities, such as pes cavus and "hammer" toe and reduced or absent muscle reflexes. HNPP most often begins in the adolescence and typically presents in the form of transient and recurrent focal mononeuropathies with motor and sensory symptoms and signs in the anatomical distribution of the affected nerve. Nerve conduction studies (NCS) show a uniform decrease in nerve conduction in CMT1A. NCS findings in HNPP show a diffuse, sensorimotor, demyelinating polyneuropathy with conduction blocks and temporal dispersion at the sites of compression (medial nerve in the carpal tunnel, ulnar nerve at the elbow and peroneal nerve at the fibular neck). Therapy of all hereditary neuropathies, including CMT1A, is limited to symptomatic therapy, thus, physical therapy, corrective surgical interventions, orthoses, and neuropathic pain therapy can be useful. The current approach to managing HNPP revolves around preventing damage to peripheral nerves caused by compression or stretching during prolonged activities and postures. Protective pads at the elbows or knees can be useful to prevent compression and nerve injury, while corticosteroids and physical therapy are indicated in the acute phase of the disease. The development of disease modifying therapies in CMT1A and HNPP is still ongoing.
Keywords: hereditary neuropathy; PMP22; Charcot-Marie-Tooth neuropathy 1A; hereditary neuropathy with liability to pressure palsies